1997
DOI: 10.1111/j.1349-7006.1997.tb00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Azoxymethane‐initiated Colon Tumor by Bovine Lactoferrin Administration in F344 Rats

Abstract: The influence of bovine lactoferrin (bLF) on colon carcinogenesis was investigated in male F344 rats treated with azoxymethane (AOM). Following three weekly injections of AOM, the animals received 2 or 0.2% bLF for 36 weeks. No effects indicative of toxicity were noted, but significant reduction in both the incidence and number of adenocarcinomas of the large intestine was observed with both doses. Thus, the incidences of adenocarcinomas in the groups receiving 2% and 0.2% bLF were 15% and 25%, respectively, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 13 publications
2
55
0
Order By: Relevance
“…1,2) Recently, bovine lactoferrin (bLF) was shown to strongly inhibit development of colon aberrant crypt foci (ACF) and tumors induced by azoxymethane in rats without any toxic effects in major organs. 3,4) Similar effects of bLF were also observed on lung, esophagus, tongue and bladder carcinogenesis in rats. [5][6][7] The results so far obtained thus indicate that bLF is a promising chemopreventive agent for carcinogenesis, although the underlying mechanisms remain unclear.…”
Section: Abstract: Lactoferrin -Cyp1a2 -Meiqx -Liver Carcinogenesissupporting
confidence: 55%
“…1,2) Recently, bovine lactoferrin (bLF) was shown to strongly inhibit development of colon aberrant crypt foci (ACF) and tumors induced by azoxymethane in rats without any toxic effects in major organs. 3,4) Similar effects of bLF were also observed on lung, esophagus, tongue and bladder carcinogenesis in rats. [5][6][7] The results so far obtained thus indicate that bLF is a promising chemopreventive agent for carcinogenesis, although the underlying mechanisms remain unclear.…”
Section: Abstract: Lactoferrin -Cyp1a2 -Meiqx -Liver Carcinogenesissupporting
confidence: 55%
“…Recently, we have shown that bLF inhibits the development of AOM-induced aberrant crypt foci (precursor lesions) 9) and carcinomas 10) in the rat colon when given as 20) Furthermore, we have observed activation of NK activity in AOM-treated rats fed bLF. 8) Findings have accumulated pointing to a wide array of functions of bLF in the immune system; thus NK cell activation, 5) stimulation of LAK cell activity 6) and potentiation of macrophage cytotoxicity 7) have been documented, Many compounds have been demonstrated to exert chemopreventive effects.…”
Section: Discussionmentioning
confidence: 71%
“…We have recently shown that dietary supplementation with bovine lactoferrin (bLF), derived from bovine milk, 2) can inhibit the development of azoxymethane (AOM)-induced aberrant crypt foci (ACF) as precursor lesions of tumor development, 9) as well as carcinomas 10) in the rat colon, without any toxic effects in major organs. It was also found to reduce growth and metastasis of solid tumors.…”
mentioning
confidence: 99%
“…Recently, some studies have suggested chemopreventive and antitumor activity for lactoferrin as well. In rat models, lactoferrin treatment significantly reduced azoxymethane-induced colonic carcinogenesis, as well as N-butyl-N- (4-hydroxybutyl)nitrosamine-induced bladder carcinogenesis (2,3). In addition, Bezault et al (4) found that lactoferrin reduced solid tumor growth and strongly inhibited experimental metastasis in mice.…”
Section: Introductionmentioning
confidence: 97%